Analysis of influential factors of stent-related adverse events after percutaneous coronary intervention more than twice: a single-center retrospective study - Jing Li; Yu Liang; Pengfei Chen (Scientific Reports)
Abstract We aimed to assess the factors affecting patient outcomes in multiple stent placements over a 10-year period. The single-center study included 1,200 patients who had multiple stents implanted at least twice or more. Participants were divided into the adverse outcomes as endpoints (n = 204 [17%]) and control groups. Univariate and multivariate analyses of stent-related adverse events risk during 10 years and logistic regression analysis of the adverse outcomes risk factors were performed. Univariate analysis revealed the impact of acute coronary syndrome (ACS), diabetes mellitus, hypertriglyceridemia, cumulative lesions in the left anterior descending (LAD) and left circumflex (LCX) arteries, number of stents in the LAD, LCX, and right coronary artery (RCA), presence of multiple coronary artery lesions, total number of stents used, and intervals between the first and second and between the fourth and fifth implantations. For secondary stent implantation, significant factors in univariate analysis included the number of LAD and LCX lesions, stents in LAD, LCX, and RCA, extent of coronary lesions, ACS, hypertension, diabetes, and total stent count. Many factors affect the outcomes in this patient group over time. Reducing the need for frequent percutaneous coronary intervention and considering the number of stents implanted are essential to improving outcomes.